Web development with Bootstrap 4 and Angular 2 : combine the power of Bootstrap 4 and Angular 2 to build cutting-edge web apps that truly stand out from the crowd /: combine the power of Bootstrap 4 and Angular 2 to build cutting-edge web apps that truly stand out from the crowd. (2016) - Akopkohyants, Sergey; Radofrd, Stephen
No abstract available